2017
DOI: 10.1001/jama.2017.9414
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clinical Studies Used for US Food and Drug Administration Approval of High-Risk Medical Device Supplements

Abstract: Among clinical studies used to support FDA approval of high-risk medical device modifications, fewer than half were randomized, blinded, or controlled, and most primary outcomes were based on surrogate end points. These findings suggest that the quality of studies and data evaluated to support approval by the FDA of modifications of high-risk devices should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
(64 reference statements)
3
28
1
Order By: Relevance
“…The US studies were also restricted to certain groups of high-risk devices. In general, the proportion of RCTs ranged between 27% and 45%,12 13 16 which is less than half of the proportion in the present study. Under both regulations, there is a clear time trend towards higher-level evidence.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The US studies were also restricted to certain groups of high-risk devices. In general, the proportion of RCTs ranged between 27% and 45%,12 13 16 which is less than half of the proportion in the present study. Under both regulations, there is a clear time trend towards higher-level evidence.…”
Section: Discussioncontrasting
confidence: 68%
“…Besides safety and performance, the manufacturer has to show that the use of the device has ‘acceptable risks when weighed against the benefits’ 9. Previous studies have found large differences between study designs, with the proportion of randomised controlled trials (RCTs) ranging from less than 10%11 to about 50%,12 depending on device type, risk class and regulatory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis on quality of clinical studies and data used to support FDA approval of high-risk medical devices by Zheng et al showed that fewer than half were randomized, blinded or controlled and most primary endpoints were surrogates. 8 For Lariat, controlled trials against DOACs are necessary, but asking for a comparator trial against Watchman is overzealous since the number of patients required to establish even a wide margin of noninferiority would make the trial impossible. At this point in time, many of us who clamor for statistical power would accept smaller numbers in a study that took on the question of what to do with the patients who have absolute contraindications to anticoagulation, a desperately unmet medical need.…”
Section: Editorial Commentmentioning
confidence: 99%
“…A recent analysis on quality of clinical studies and data used to support FDA approval of high‐risk medical devices by Zheng et al. showed that fewer than half were randomized, blinded or controlled and most primary endpoints were surrogates . For Lariat, controlled trials against DOACs are necessary, but asking for a comparator trial against Watchman is overzealous since the number of patients required to establish even a wide margin of noninferiority would make the trial impossible.…”
mentioning
confidence: 99%
“…The past year was a troubling year for failed technology, as both the lay press [1] , [2] and also an orthopaedic surgeon [3] reported troubling flaws in the United States Food and Drug Administration (FDA) post-market surveillance program. Scientific analysis further showed that reporting flaws and inadequacies affect response even when adverse events are reported [4] , and the FDA has limits as far as the available research when making approval decisions [5] .…”
mentioning
confidence: 99%